Direct GaAs Nanowire Growth and Monolithic Light‐Emitting Diode Fabrication on Flexible Plastic Substrates. Issue 8 (23rd March 2022) - Khayrudinov, Vladislav; Sorokina, Anastasiia; Raj, Vidur; Gagrani, Nikita; Koskinen, Tomi; Jiang, Hua; Tittonen, Ilkka; Jagadish, Chennupati; Hoe Tan, Hark; Lipsanen, Harri; Haggren, Tuomas
Abstract : The growth of self‐catalyzed GaAs nanowires (NWs) and monolithic light‐emitting diode (LED) directly on flexible plastic substrates is reported. Dense GaAs NW forest is attained in self‐catalyzed mode using metalorganic vapor phase epitaxy. The NWs are shown to be crystalline with a zinc‐blende phase. The optical properties of the GaAs NWs are found to be promising in both photoluminescence emission and light‐trapping based on reflectance and transmittance measurements. The LED is fabricated from p‐type NWs by depositing Au as Ohmic contact and TiO2 /ITO as an electron‐selective contact. The demonstrated NW growth and LED fabrication represent a significant step toward low‐cost, industrially feasible flexible III–V NW optoelectronic applications, as plastic is inexpensive, and the fabrication steps are compatible with roll‐to‐roll processing. Abstract : Herein, the growth of self‐catalyzed GaAs nanowires (NWs) and monolithic light‐emitting diode (LED) directly on flexible plastic substrates is reported. The optical properties of the GaAs NWs are promising in both photoluminescence emission and light‐trapping based on reflectance and transmittance measurements. The demonstrated NW growth and LED fabrication represent a significant step toward low‐cost, industrially feasible flexible III–V NW optoelectronic applications.